CREATIVITY TECHNIQUES AND ACTIVATION OF THE DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP - STASOVSKYI, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the use of creativity techniques by companies in the process of creating innovative products and services. The examples of companies Samsung and IDEO are considered. It is determined how the above-mentioned companies work on creating innovations, how they use creativity techniques or their varieties for more effective generation of ideas. How companies create an innovative culture, units to work on complex problems. The use of the Theory of solving inventive tasks (TRIZ), Design-thinking is considered on specific examples.It is shown how the identification and work with limitations, the creation of multidisciplinary teams affect the results of innovation creation, the peculiarities of the approach to the development of innovations in Samsung, Google and Apple companies are considered. Factors affecting the success of using creativity techniques in innovative entrepreneurship were investigated.The author offers his own classification of factors that affect the effectiveness of using creativity techniques in innovative entrepreneurship. It is proposed to divide it into three types: internal, external and combined.The proposed classification of factors singles out individual elements that affect the effectiveness of using creativity techniques in innovative entrepreneurship, and divides them into types. This gives an understanding of whether the company's influence on a specific factor is possible, if it is internal, or partial influence, if the factor is classified as mixed, or whether it is necessary to adapt to factors on which there is no influence. Classification allows you to single out each element and work on it qualitatively. Having worked out each of the elements, the company can significantly improve the quality of innovative developments.Reconstruction of the Ukrainian economy is impossible without the creation of innovative products and services. It is the knowledge and use of appropriate creativity techniques that should become the key to the development of innovative entrepreneurship in Ukraine.
Keywords: creativity techniques; innovations; development of innovations; innovative entrepreneurship; TRIZ; Design thinking